(untitled) (Journal of the College of Basic Education, 2022)
The play consists of a group of elements, the most important of which is the text, the actor and the audience. The theorists have given priority to the text over the other elements as the basis for the composition of the theatrical work, but with the emergence of modern theatrical directorial trends, such as the theater of cruelty, the poor theater, the theater of the image, etc., which called for the marginalization of the role of The text, so it contributed to giving the motive to leave theatrical authorship, and Arab and Iraqi theater directors were affected by these trends in formulating their theatrical performances, and among these directors (Salah Al-Qasab), (Awni Karumi) and (Shafiq Al-Mahdi), and perhaps the new dealings of directors with theatrical text have a role In the limited number of Iraqi local theatrical texts, which prompted the researcher to seek to uncover the role of directing in the manufacture of the theatrical text crisis in Iraq, so the problem was crystallized under the title